Temporal Dynamics of Cognitive–Emotional Interplay in Moral Decision-making - Sarlo, Michela; Lotto, Lorella; Manfrinati, Andrea; Rumiati, Rino; Gallicchio, Germano; Palomba, Daniela (Journal of cognitive neuroscience, 2012)
This study investigated the temporal dynamics of emotional and cognitive processing underlying decision-making in moral judgment. Thirty-seven participants were presented with a set of 60 dilemmas varying in whether killing one individual was an intended means to save others (instrumental dilemmas) or a foreseen but unintended consequence (incidental dilemmas). Participants were required to decide between Options A (letting a specific number of people die) and B (killing one person to save a specific number of people). ERPs were recorded to a slide displaying the letters A and B while subjects were deciding between the options, and movement-related potentials were recorded time-locked to the behavioral response, thus allowing the investigation of both stimulus- and response-related processes during decision-making. Ratings of emotional valence and arousal experienced during decision-making were collected after each decision. Compared with incidental dilemmas, instrumental dilemmas prompted a lower number of B choices and significantly more unpleasant decisions. A larger P260 component was found in the frontopolar and frontal areas when subjects were deciding on instrumental than incidental dilemmas, possibly reflecting an immediate affective reaction during the early stage of assessment and formation of preferences between available options. On the other hand, decisions on incidental dilemmas required greater attentional resources during the fairly controlled later processing, as reflected in the larger slow wave amplitudes. In addition, facilitation of action selection and implementation was found for incidental dilemmas during the second stage of decision-making, as supported by the larger amplitudes of both components of the Bereitschaftspotential.